PERAN PEMBINA ASRAMA TERHADAP STRESS ACADEMIC SANTRI DI PONDOK PESANTREN SUMATERA THAWALIB PARABEK BUKITTINGGI - Thaheransyah Thaheransyah; Rosdialena Rosdialena; Isro Diin (Pusat Studi Penelitian dan Evaluasi Pembelajaran, 2023)
This research was motivated by the problems found in the Sumatra Thawalib Parabek Bukittinggi Islamic Boarding School. Students who feel academic stress due to many demands from parents and schools, such as encouragement for achievement in students in academic learning outcomes. In this case, there are many failures that students do find difficult due to the limited abilities of students. While the purpose of this study is to describe how the role of dormitory coaches on the academic stress of students at the Sumatra Thawalib Parabek Bukittinggi Islamic Boarding School. The research method used is qualitative descriptive research. The subjects of this study were dormitory supervisors aged 20-30 years and students aged 14-16 years as many as 10 people. How to take research subjects using total sampling techniques. Data collection techniques in this study by conducting observations, interviews and documentation. The results of this study show that the role of dormitory coaches on student academic stress from cognitive aspects, affective aspects, physiological aspects, and behavioral aspects has a positive impact on students, this is indicated when students can improve student learning outcomes at school